TEACHING ENGLISH TO CHILDREN: CHALLENGES TO OVERCOME AND KNOWLEDGE TO MASTER - Tutida, Alessandra Ferraz; Tonelli, Juliana Reichert Assunção (fólio - revista de letras, 2018)
English language teaching to children (ELTC) is in constant expansion in the Brazilian and international educational context (ROCHA, 2007; TONELLI, 2007; LINGUEVIS, 2007; TONELLI and CRISTOVÃO, 2010, CAMERON, 2003). Despite this growth, flaws in the teacher education of this area (CRISTOVÃO and GAMERO, 2009), as well as lack of parameters to guide this work (BENEDETTI and SANTOS, 2009) are witnessed. This paper intends to analyze the curriculum of the public universities in the state of Paraná that offer English and/or Portuguese/Languages course in order to look for changes that try to meet the needs of this specific educational area, as well as to investigate some of the knowledge teachers need to master in order to work with ELTC. Results show that the modifications in the universities' curriculum were not significant. Moreover, data show that there is specific knowledge and a particular profile that are desirable for this teacher.